The Utilization of Snakehead Fish (Channa Striata) and Tempeh in Making of Tofu Skin Rolls as a High Protein Energy Food for KEP Children - Rosyida, Faridatur (Jurnal Gizi dan Kesehatan Nusantara, 2024)
AbstractProtein energy deficiency is a problem of malnutrition where sufferers do not consume enough foods that are high in energy and high in protein so that their daily energy and protein needs are not met. The aim of this research is to (1) determine the effect of snakehead fish and tempeh treatment on the level of preference for tofu skin rolls as TETP food for KEP children, (2) determine the energy, carbohydrate, protein and fat content from the results of the best sensory tests on tofu skin rolls. snakehead fish and tempeh as TETP food for KEP children. This research used experimental research with 3 treatments, namely F1 (A007) with 60% snakehead fish and 40% tempeh, F2 (A018) with 70% snakehead fish and 30% tempeh, F3 (A021) with 80% snakehead fish and 20% tempeh. The non-parametric statistics of the Kruskal Wallis test and continued with Mann Whitney will be used to analyze the data from the sensory test results. The results of statistical analysis show that tofu skin roll F3 (A021) using 80% snakehead fish and 20% tempeh is the best treatment with an average value of 5.10. The use of snakehead fish and tempeh affects the level of preference for color, aroma, taste but does not affect the texture of the tofu skin roll. The nutritional content of the best formula F3 (A021) per 100 grams is energy of 173.65 kcal, protein of 12.62%, carbohydrates of 11.33% and fat of 8.65%.Keywords: Tofu Skin Roll, Snakehead Fish, Tempe, KEP.